2016
DOI: 10.1002/ccd.26716
|View full text |Cite
|
Sign up to set email alerts
|

Impact of proton pump inhibitors and dual antiplatelet therapy cessation on outcomes following percutaneous coronary intervention: Results From the PARIS Registry

Abstract: In clopidogrel treated PCI patients, the 2-year adjusted risk of MACE and NACE was significantly higher in PPI users driven by higher TLR compared to non-PPI users, without a difference in bleeding. PPI use was associated with lower incidence of DAPT disruption without an increase in disruption related bleeding compared to non-PPI users on DAPT. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
0
25
1
3
Order By: Relevance
“…[ 1 ] Nonetheless, antiplatelet therapy is also associated with increased bleeding risk, and gastrointestinal bleeding accounts for a notable proportion of the bleeding complications of DAPT and probably leads to DAPT cessation, which further increases adverse cardiovascular events. [ 2 ] Proton-pump inhibitors (PPIs) are often concomitantly prescribed to patients in combination with DAPT to help reduce the occurrence of gastrointestinal bleeding. [ 3 ] However, several pharmacokinetic studies and observational studies have demonstrated potential interaction of PPIs with clopidogrel via competition with liver cytochrome P450 isoenzymes (especially CYP2C19), leading to reduced antiplatelet activity and increased ischemic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Nonetheless, antiplatelet therapy is also associated with increased bleeding risk, and gastrointestinal bleeding accounts for a notable proportion of the bleeding complications of DAPT and probably leads to DAPT cessation, which further increases adverse cardiovascular events. [ 2 ] Proton-pump inhibitors (PPIs) are often concomitantly prescribed to patients in combination with DAPT to help reduce the occurrence of gastrointestinal bleeding. [ 3 ] However, several pharmacokinetic studies and observational studies have demonstrated potential interaction of PPIs with clopidogrel via competition with liver cytochrome P450 isoenzymes (especially CYP2C19), leading to reduced antiplatelet activity and increased ischemic events.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] However, several pharmacokinetic studies and observational studies have demonstrated potential interaction of PPIs with clopidogrel via competition with liver cytochrome P450 isoenzymes (especially CYP2C19), leading to reduced antiplatelet activity and increased ischemic events. [ 2 4 5 6 7 8 ] New evidences showed that the interaction may have no clinical significance. [ 9 10 ] Limited by the controversial conclusions, the 2016 American College of Cardiology/American Heart Association guideline on DAPT in patients with coronary artery disease suggested no routine PPI use in the setting of DAPT.…”
Section: Introductionmentioning
confidence: 99%
“…There was some evidence demonstrating that PPIs may not safe for long‐term use, especially in patients with CVD . For instance, a large multicenter cohort study in 2017 demonstrated that the 2‐year adjusted risk of major adverse cardiovascular events in patients taking dual antiplatelets was significantly higher in PPI users than in non‐PPI users, without a difference in bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…There was some evidence demonstrating that PPIs may not safe for long‐term use, especially in patients with CVD . For instance, a large multicenter cohort study in 2017 demonstrated that the 2‐year adjusted risk of major adverse cardiovascular events in patients taking dual antiplatelets was significantly higher in PPI users than in non‐PPI users, without a difference in bleeding . Furthermore, a recent meta‐analysis of observational studies in 2018 showed an increased risk of any adverse cardiovascular event in the PPI monotherapy group than in the non‐PPI group (relative risk 1.25; 95% CI 1.11–1.42; P < 0.001), independent of the use of clopidogrel; however, the result became insignificant when analyzing the data from RCTs (relative risk 0.89; 95% CI 0.34–2.33; P = 0.85) .…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAPT) mitigates the risk of coronary stent thrombosis and ischemic events among patients underwent percutaneous coronary intervention (PCI) . Nonetheless, antiplatelet therapy is also associated with increased bleeding risk, and gastrointestinal bleeding (GIB) accounts for a notable proportion of bleeding complications of DAPT . In‐hospital GIB complicating PCI has been shown to be associated with short‐term mortality .…”
Section: Introductionmentioning
confidence: 99%